Implementation of environment-based learning model at the elementary education level: a systematic literature review - Suhartono, Suhartono; Salimi, Moh; Hidayah, Ratna; Fauziah, Muna; Jupriyanto, Jupriyanto (Jurnal Ilmiah Pendidikan Dasar, 2025)
Literature reviews on the implementation of environmental-based learning models at the elementary education level are still very limited. This study uses a systematic literature review method on the implementation of environmental-based learning models at the elementary education level. The research data was taken from the Scopus and Google Scholar databases, which are the main sources of information. The data was processed using the PRISMA method. In data collection, there are several keywords used such as "environment learning", "model of learning environment", "environment-based learning models", "nature-based learning model", "environmental-based learning model", and "model of environment education". Data were analyzed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with data identification, screening, and determination steps. The results of this study indicate that the application of environmental-based learning models has been widely studied and implemented in various contexts and different subjects in various countries. Of the 16 articles identified, 81.25% were written in English and there was an increase in research between 2021 and 2023. This study shows that the use of environmental-based learning models is often used in science. In addition, qualitative research dominates in this study, while elementary school students are the subjects who often study it. Indonesia is the country with the largest number of studies. The findings of this study have implications for the classroom learning process so that teachers can apply the model with evidence of increased student competence at the elementary education level.